Sie sind auf Seite 1von 96

 R n C n

V n K ϕ : V V B V [ϕ] B ϕ B ϕ 2 t 2 + 1 = 0 ±i

V n K ϕ End(V )

V n K ϕ : V V ϕ A

 B = (v 1 , v 2 , , v n )

V

ϕ(v j ) =

n

i=1

a ij v i

(j = 1,

, n).

ϕ B (n×n)

[ϕ] B = A := (a ij )

A B A A

ϕ V [ϕ] B B [ϕ] C B C ϕ B C A = [ϕ] C B C

B

B

A = [ϕ]

B

C =

 

1

0

0

0

1

···

···

0

0

0

1

0

0

···

···

···

···

···

···

0

0

0

···

···

···

···

···

···

0

0

0

B = C [ϕ] B

A = diag(λ 1 ,

,

λ n ) :=

λ

1

λ

n

λ 2

  .

 

ϕ B diag(λ 1 ,

ϕ(v j ) = λ j v j

j = 1,

, n.

, λ n )

v 1 ,

, v n V ϕ(v j ) = λ j v j

λ j K (j = 1,

, n) v j λ j

V = R 2 g 0

σ g v 1 g v 2 g

σ(v 1 ) = 1 · v 1

,

σ(v 2 ) = (1) · v 2 .

v 2

σ v 1 , v 2

1

π g v 1 v 2

A =

1

0

0

σ(v 1 ) = 1 · v 1 ,

σ(v 2 ) = 0 = 0 · v 2 .

A v 1 , v 2

A =

1

0

0

0 .

g

v 1

σ(v 1 )=1·v 1

σ(v 2 )=(1)·v 2

ρ θ : R 2 −→ R 2 θ ]0, π[ λ R

ϕ(v) = λv

 ϕ(v) = λv ⇐⇒ ϕ(v) − λv = 0 ⇐⇒ ϕ(v) − λ id(v) = 0 ⇐⇒ (ϕ − λ id)(v) = 0 ⇐⇒ v ∈ ker(ϕ − λ id).

id = id V V v V ϕ(v) = λv λ K v λ

ϕ End(V ) V λ K ϕ 0 = v V

ϕ(v) = λv

v = 0 ϕ λ

V λ := V λ (ϕ) := ker(ϕ λ id V ) = {v V : ϕ(v) = λv}

λ V λ V

d λ := dim V λ 1

0 0 λ λ

λ

λ K V λ (ϕ) = {0} d λ 1 V λ (ϕ) \ {0} ϕ λ

ϕ V ϕ B [ϕ] B

A M n (K) (n × n)

ϕ A End(K n ),

x

Ax.

λ K A λ ϕ A

0

Ax = λx

= x K n

ker(ϕ A λ id) = {x K n : Ax = λx}

A λ

A ϕ A K n A

ϕ : V V

λ ϕ

⇐⇒ (ϕ λ id)(v) = 0 v = 0

⇐⇒ ker(ϕ λ id)

= {0}

v ϕ λ

⇐⇒ v (ϕ λ id)v = 0

⇐⇒ 0

= v ker(ϕ λ id)

A M n (K) λ K A

(A λE)v = 0

v = 0 λ Av = λv

 Av = λv ⇐⇒ Av − λv = 0 ⇐⇒ Av − λEv = 0 ⇐⇒ (A − λE)v = 0

E = E n n×n

ϕ End(V ) dim V < λ K ϕ det(ϕ λ id) = 0

V

 ker( ϕ − λ id) = { 0 } ⇐⇒ ϕ − λ id ⇐⇒ ϕ − λ id ⇐⇒ det(ϕ − λ id) = 0

A M n (K)

λ A ⇐⇒ A λE

⇐⇒

det(A λE) = 0

A

A λE det(A λE) = 0 ϕ A : K n K n , x Ax

det(A λE) = det(ϕ A λ id),

A λE ϕ A λ id K n

g

σ

v 1

λ 1 = 1

λ 2 = 1

v 2

V λ 1 = R v 1

g g

V λ 2 = R v 2

π g

λ 1 = 1

λ 2 = 0

1

A := 1 0

0 1 M 2 (R).

λ R

A λE = λ 1

λ

1

det(A λE) = λ 2 + 1

= 0.

A λE A A

A := 1 0

0 1 M 2 (C).

0 = det(A λE) = λ 2 + 1

λ 1 = i λ 2 = i

(A λ j E)v = 0

v 1 = 1

i

v 2 =

i .

1

K = R A =

1

3

A λE = 1 λ 3

3

1 λ

3

0 = det(A λE) =

1 λ

3 1 λ

= (1 λ) 2 9

λ 1/2 = 1 ± 3

λ 1 = 4,

λ 2 = 2.

3

1

λ 1 = 4

λ 2 = 2

(A λ 1 E)v = 3

3

(A λ 2 E)v = 3

3

3 v = 0

3

3 3 v = 0

=

v R 1 1 .

=

v R

1 .

1

v 1 = 1 1 v 2 = 1 A B R 2

A ϕ A : R 2 R 2 A B

1

A = 4 0

2

0

B = (v 1 , v 2 ) Av 1 = 4v 1 Av 2 = 2v 2 A A

A = S 1 AS

1 1

S v 1 , v 2

(e 1 , e 2 )

S S = 1

1

λ 1 , λ 2 ,

v 1 ,

, λ r ϕ End(V ) v 1 ,

, v r

, v r

k = 1 v 1 ,

µ 1 v 1 +

ϕ

k v 1 ,

+

, v k

, v k1

µ k v k = 0.

0 = ϕ(µ 1 v 1 +

+

µ k v k ) = µ 1 ϕ(v 1 ) +

+

µ k ϕ(v k ) = µ 1 λ 1 v 1 +

+

µ k λ k v k .

λ k

0 = µ 1 (λ 1 λ k )v 1 +

+ µ k1 (λ k1 λ k )v k1 ,

v 1 ,

, v k1

µ j (λ j λ k ) = 0,

j = 1,

, k 1.

λ j = λ k µ j = 0 µ k v k = 0 µ k = 0 v k

0

λ 1 , λ 2 ,

, λ r

V λ 1 + V λ 2 +

+ V λ r = V λ 1 V λ 2

ϕ

V λ r .

u

u

= u 1 +

= u 1 +

+

+

u r1 + u r

r1 + u r

u

u u i , u i V λ i u i = u

i = 1,

, r

i

0 = (u 1 u 1 ) +

+ (u r1 u r1 ) + (u r u r ).

u j u j 0 λ j 0 0

u j = u j j

ϕ n V

n ϕ λ 1 ,

v 1 ,

, λ r

, v r r n

A M n (K) n A

, v n

K n A

λ 1 ,

, λ n A v 1 ,

λ 1 ,

d i V λ i V λ 1 ⊕· · ·⊕V λ r d 1 +d 2 +···+d r = n V V ϕ

ϕ

, d r

, λ r ϕ d 1

d 1

d r

λ 1
0
0
λ 1

λ r

0

0

λ r

A M n (K)

ϕ A : K n K n , x Ax

 λ 1 λ 2 λ r n×n A d 1 , d 2 , , d r A V λ 1 + V λ 2 + ··· + V λ r = V λ 1 ⊕ V λ 2 ⊕ ··· ⊕ V λ r . v 1 , v 2 , , v r λ 1 , λ 2 , , λ r

r n n×n A n

A M n (C ) v C n

A λ C v A λ

v C n v

K

p(t) = a 0 + a 1 t +

+

a n t n ,

t K p K K

a: N 0 K,

m

a m .

N N a m = 0 m > N

(a 0 , a 1 ,

, a N , 0, 0,

.).

t n n N 0

t n (m) := δ nm =

1

0

n = m

a

a =

N

n=0

a n t n .

t n

K[t] = span{t n : n N 0 }

p(t) =

N

n=0

a n t n = a 0 + a 1 t +

+ a N t N

p(t) t t K[t] K[t] t n n N 0 1 t 0 a 0 t 0 = a 0 K[t] p(t) t p(t) p t

= 0 deg(p(t)) := N

p(t) = a 0 +

+ a N t N

K[t] a N

p a N p(t) deg(0) := −∞ deg(t n ) = n n N 0 p(t) N a m = 0 m > N

p(t) =

M

n=0

a n t n

M > N t n n N 0

p(t) =

N

n=0

a n t n

a 0 = b 0 , a 1 = b 1 ,

q(t)

=

N

n=0

b n t n

, a N = b N

p(t) = a 0 + a 1 t +

p : K K,

x

a 0 + a 1 x +

Φ: K[t] → P(K),

p

+

p

a n x n

+ a n t n K[t]

K = Z/2Z x 2 = x 0, 1 K Φ(t n ) = Φ(t) n 1

p 1 (t) = t

p 2 (t) = t 2

K K

Φ K q(t) ker Φ q : K K n n K Φ Q R C

K[t] t

(a 0 + a 1 t +

+ a N t N ) + (b 0 + a 1 t +

+ b N t N )

= (a 0 + b 0 ) + (a 1 + b 1 )t +

+ (a N + b N )t N

λ · (a 0 + a 1 t +

+ a N t N ) = λa 0 + λa 1 t +

+ λa N t N .

(a 0 + a 1 t +

+ a N t N ) · (b 0 + a 1 t +

:= a 0 b 0 + (a 0 b 1 + a 1 b 0 )t +

+

i+j=n

+ b M t M )

a i b j t n +

+ a N b M t N+M .

K[t] t K K 1 := t 0

λ · (p · q) = (λ · p) · q = p · (λ · q)

λ K p, q K[t]

p q

deg(p + q) max(deg(p), deg(q))

deg(p)

= deg(q)

deg(p · q) = deg(p) + deg(q).

p(t) = a 0 + a 1 t +

+ a N t N ,

q(t) = b 0 + b 1 t +

+ b M t M

a N = 0 b M = 0

M N p(t) + q(t)

p(t) + q(